USE OF A NUMERICAL ANALYTICAL MODEL FOR ASSESSING THE FUNCTIONAL EFFECTIVENESS OF AN INFORMATION PROTECTION SYSTEM BY ANALYSING ITS PROBABILISTIC-TEMPORAL CHARACTERISTICS - V. P. Alferov; A. V. Butskikh; A. V. Krisilov; A. D. Popov; E. A. Rogozin (Вестник Дагестанского государственного технического университета: Технические науки, 2020)
Abstract. Aim Currently, the implementation of computational experiments to determine the probabilistic-temporal characteristics of protection functions for automated information systems is a complex and costly task. In order to study the dynamics of transitions between the states of this type of system, it is necessary to develop a mathematical model and an algorithm for computing the corresponding characteristics.Method. To achieve this goal, a mathematical model of the information security system was developed in the MATLAB software environment. The main advantages of this software environment consist in a high level of visualisation, the ability to modify models to analyse other systems of this type and the availability of integration tools with other software products.Results. The article presents a numerical and analytical model of a system for protecting information from unauthorised access. The functional dynamics of the system are described using a stochastic Petri net. In order to solve the integral equations and determine the probabilities of reaching the final state in a given time, the Laplace transform is used. The solution is carried out in an analytical mode to obtain an explicit form of the dependences of the probability-time characteristics of the system on the probabilities of transitions between states and the average times the system stays in each state. The paper presents the results of calculating the probability-time characteristics of the “Turning on the personal computer and user identification” subsystem of the “Guard NT” system for preventing unauthorised access to information.Conclusion. The developed model, which can be used to study the dynamics of transitions between states of an information protection system against unauthorised access in an automated system, as well as to optimise the time it takes to complete functional tasks, can also be used to improve the operational efficiency of these systems.